Conceptualising the relationship between integration needs and integrations technologies adoption: comparing cases of SMEs with a large organisation. (11th April 2007) - Chen, Hsin; Dwivedi, Yogesh Kumar
This paper proposes a novel conceptual model that (1) it identifies in what ways does SMEs' integration needs differ from large companies, and (2) it explores how the relationship between SMEs' and large organisations' integration needs affect their integration technologies adoption decisions-making. This model is significant' as it (1) extends existing integration technologies adoption literature by incorporating the different integration needs between SMEs and large counterparts, and (2) enhances the decision making in this area, by supporting a more detailed level of analysis of the integration technologies adoption between SMEs and large organisations.